Possible association between acetazolamide administration during pregnancy and multiple congenital malformations - Al-Saleem AI; Al-Jobair AM (Dove Medical Press, 2016)
Afnan I Al-Saleem,1 Asma M Al-Jobair21Dental Department, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 2Department of Pediatric Dentistry and Orthodontics, College of Dentistry, King Saud University, Riyadh, Saudi ArabiaAbstract: Congenital malformations might occur because of environmental or genetic factors, and sometimes occur because of unknown causes. Acetazolamide is a carbonic anhydrase inhibitor that is used to treat idiopathic intracranial hypertension, glaucoma, and epilepsy. The use of acetazolamide has not been recommended for pregnant women because of reported teratogenic risks. Congenital malformations, such as ectrodactyly, syndactyly, cleft lip/palate, and retarded incisor teeth development, have been reported in experimental animals. However, tooth agenesis due to the use of acetazolamide has not been reported yet. Oligodontia is a severe type of tooth agenesis involving six or more congenitally missing teeth. The causes of oligodontia are attributed to environmental factors, such as irradiation, drugs, trauma, tumors, infection, genetic factors, or a combination. There is no credible evidence of undesirable effects of acetazolamide use in human pregnancy. However, we report a case of a 12-year-old Saudi boy who was exposed to maternal acetazolamide (1,000 mg/day) for treatment of idiopathic intracranial hypertension before pregnancy, during the first trimester, and throughout the pregnancy. This treatment might have resulted in some congenital malformations, such as ectrodactyly, syndactyly, and oligodontia.Keywords: acetazolamide, oligodontia, ectrodactyly, syndactyly